Monitoring strategies for “Ponta da Ferraria e Pico das Camarinhas” geosite (S. Miguel Island, Azores) - Lima, A. (2012)
This paper presents an ongoing work that is being developed under the scope of a master thesis. “Ponta da Ferraria e Pico das Camarinhas” is a protected area and a geosite with high geological relevance in S. Miguel Island, Azores archipelago, Portugal. Because of its importance for the Azores Geopark geoconservation strategy, a monitoring work has been under development during the last year in order to assure that the main geological features of the geosite are preserved, even considering its present use. Among the many geological features of the geosite the littoral cone (or pseudocrater) is the most endangered due to its uniqueness and high vulnerability. The monitoring strategy also intends to assess how visitors evaluate the interpretative panel located in the geosite based on visitors’ opinions. The number of visitors is being determined by direct counting and the visitors’ profile is being outlined based on data obtained with short questionnaires.